PHENOLOGICAL DEVELOPMENT FEATURES OF VACCINIUM х COVILLEANUM (VACCINIACEAE) VARIETIES INTRODUCED IN THE SOUTHERN AGRICLIMATIC REGION OF THE REPUBLIC OF BELARUS - S. L. Prikhodko (Труды по прикладной ботанике, генетике и селекции)
Belarusian Polesia is a favorable region for successful introduction of the studied varieties of northern highbush blueberry. In the area of the trials the amount of positive temperatures and the length of the growing period are sufficient for the introduced plants to complete their full growing cycle.